2002
DOI: 10.1002/jmri.10130
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the forefoot under weight‐bearing conditions: Position‐related changes of the neurovascular bundles and the metatarsal heads in asymptomatic volunteers

Abstract: Purpose:To assess practicability of weight-bearing magnetic resonance (MR) imaging of the forefoot, and to demonstrate position-related changes of the neurovascular bundles and the metatarsal heads in asymptomatic volunteers. Materials and Methods:With an open-configuration MR system, 32 feet of 32 asymptomatic individuals aged 20 -60 years were studied in supine and weight-bearing body positions. Transverse T1-weighted spin-echo MR images were performed. MR images were evaluated qualitatively with regard to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The human foot is unique in having both a transverse tarsal and longitudinal metatarsal arch, which results in a half dome shape with hollow surfaces facing both downward and medially. It should, however, be noted that there is no distal (metatarsal) functional transverse arch (Cavanaugh et al, 1987;Luger et al, 1999;Weishaupt et al, 2002;Kanatli et al, 2003); it is a transverse arch more proximally in the tarso-metatarsal region. Other primates have only the transverse tarsal arch, their feet being flat in the longitudinal direction (Aiello and Dean, 1990).…”
Section: Functional Affinitiesmentioning
confidence: 98%
“…The human foot is unique in having both a transverse tarsal and longitudinal metatarsal arch, which results in a half dome shape with hollow surfaces facing both downward and medially. It should, however, be noted that there is no distal (metatarsal) functional transverse arch (Cavanaugh et al, 1987;Luger et al, 1999;Weishaupt et al, 2002;Kanatli et al, 2003); it is a transverse arch more proximally in the tarso-metatarsal region. Other primates have only the transverse tarsal arch, their feet being flat in the longitudinal direction (Aiello and Dean, 1990).…”
Section: Functional Affinitiesmentioning
confidence: 98%
“…Tendon and median nerve translation within the carpal tunnel with finger flexion and extension has been observed in vivo using MRI (2, 7). A similar MRI study monitored depth changes in NVB positioning in the forefoot during weight‐bearing exercises (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, BMLs in OA have been suggested to exhibit some degree of specificity [4]. Although most data are related to knee OA, BMLs have also been observed for other articular OA diseases [5][6][7][8]. As an example, Boutry et al [6] found BMLs in 12/12 of patients with rapidly destructive hip OA.…”
Section: Introductionmentioning
confidence: 93%